Conflict experiences of Northern Nigerian civilians - Yero, Aliyu (2015)
Peace and security are two major requirements for any human society to flourish; however the trend seems to be declining as societies are facing less peace basically from internal conflicts. In African and Nigeria in particular, civilians have had to carry on the burden of protracted conflict despite the fact that they are not conflicting with anyone. Since 2009, Northern Nigeria has been facing a decline in peace as a result of the conflict between Jama’atu Ahlis Sunnah lid da’awati wal Jihad. Regrettably, often in conflict situations, a lot of attention is given to the parties involved (the two elephants) in seeking for peace, while the civilians only assume the victim status (grasses). Subsequently, using qualitative phenomenology, one on one in-depth interview was conducted with twelve Northern Nigerian civilians who are studying in a Malaysian public university to answer two research questions; what is the living experience of Northern Nigeria civilians about the conflict currently going on? And how has these experiences shaped the meaning civilians attach to their social reality? Essentially, this study is about “reality from lived experiences”. Two sampling methods were employed to select participants in this study; the first is criterion purposive sampling which was used in identifying the first participant and followed by snowballing sampling which was used to identify the remaining participants and data collected was transcribed, coded and analysed through inductive and comparative methods. The results showed that participants have various types of experienced since the conflict began. Using the lens of human needs theory of John Burton as a guide, the study found that participants exhibit emotional experiences which have the potential of leading to psychological instability; these include sadness, intense fear, self-pity and frustration. The data further revealed that strenuous constraints hinder the realization of basic needs with little concern for prioritization. In particular, the need for identity and security is earnestly sought while meeting immediate family basic daily needs have become a challenging experience to participants. Using the constructivist viewpoint that perception is reality and building on the Social Reality theory “collective intentionality”, the study found out that the reality of life civilian’s face is entirely different from what existed before the conflict began in 2009 especially when participants consistently narrate their experiences while comparing the present and the past. Furthermore, loss have been a glaring reality that civilians have to live with which have reduced life to that of barely surviving, with the prevailing challenges experienced, results from this study have shown that civilians have come to realise that their destiny is in their hands as both the authorities and insurgents have inflicted proportional damages. Finally, civilians in this study have come to accept a reality of living life in a state which is entirely reduced to how basic needs can be attained in the face of conflicting demands of life. This study conclude that for any meaningful peace, civilian experiences must be involved in the process of making peace, building peace and keeping peace in Northern Nigeria.